What about BMX? A scoping review of injuries, risk factors, and prevention strategies - Black, A. M.; Gupta, S.; Rockcliff, C. (British Journal of Sports Medicine, 2021)
Background Bicycle motocross (BMX) was officially added to the Olympics in 2008. Participation has increased over the last decade and is listed as a top sport for injury rates in multisport studies. Before effective prevention programs can be designed and implemented, it is important to understand injury risk, risk factors and potential prevention strategies.